HOMOGENIZATION OF STELLAR CATALOGUES THROUGH DATA INTERCOMPARISON - Malyuto, V. (Одеські астрономічні публікації, 2007)
The accuracies of some selected stellar catalogues of Teff values have been estimated through data intercomparison. The technique of such estimating developed earlier for triples of catalogues has been adapted to a set of catalogues. A homogenized catalogue of Teff values has been produced by weighted data averaging and compared with some available data.